Transparent nanostructured cellulose acetate films based on the self assembly of PEO-b-PPO-b-PEO block copolymer. (1st June 2017) - Gutierrez, Junkal; Carrasco-Hernandez, Sheyla; Barud, Hernane S.; Oliveira, Rafael L.; Carvalho, Renata A.; Amaral, André C.; Tercjak, Agnieszka
Graphical abstract: Highlights: A strategy to develop nanostructured sustainable matrices using block copolymers. The addition of 40 wt% of EPE leads to nanostructured EPE/CA composite films. Preparation and characterization of highly transparent nanostructured EPE/CA films. Thermal stability and mechanical properties of EPE/CA films were investigated. Wettability and water vapor permeability were improved by blending with EPE. Abstract: In this study fabrication and characterization of transparent nanostructured composite films based on cellulose triacetate (CTA) and poly(ethylene oxide)-b-poly(propylene oxide)-b-poly(ethylene oxide) (EPE) triblock copolymer were presented. The effect of the addition of EPE triblock copolymer on the thermal stability, morphology, and mechanical properties of cellulose triacetate films was investigated. The triblock EPE was chosen since PEO blocks interact favorably with CTA, whereas, PPO blocks remain immiscible which provokes a microphase separation. This allows to obtain EPE/CTA composite films with ordered microphase-separated structures where PPO spherical microdomains are well-dispersed in PEO/CTA matrix by simple solvent-evaporation process. During this process, PEO block chains selectively interact with CTA by strong interpolymer hydrogen-bonding while PPO block microseparated. The addition even 40 wt% of EPE leads to nanostructured EPE/CTA composite. The cytotoxicity assay of CTA and EPE/CTA composite films confirm non-toxic character of designed transparent nanostructured composites based on sustainable matrices.